Highly Efficient Dehydrogenative Coupling of Hydrosilanes with Amines or Amides Using Supported Gold Nanoparticles. Issue 8 (8th January 2015) - Mitsudome, Takato; Urayama, Teppei; Maeno, Zen; Mizugaki, Tomoo; Jitsukawa, Koichiro; Kaneda , Kiyotomi
Abstract Hydroxyapatite‐supported gold nanoparticles (Au/HAP) can act as a highly active and reusable catalyst for the coupling of hydrosilanes with amines under mild conditions. Various silylamines can be selectively obtained from diverse combinations of equimolar amounts of hydrosilanes with amines including less reactive bulky hydrosilanes. This study also highlights the applicability of Au/HAP to the selective synthesis of silylamides through the coupling of hydrosilanes with amides, demonstrating the first example of an efficient heterogeneous catalyst. Moreover, Au/HAP shows high reusability and applicability for gram‐scale synthesis.